Faktor – Faktor Yang Berhubungan Dengan Gangguan Pendengaran Pada Nelayan Penyelam Tradisional Di Negeri Haya Kecamatan Tehoru - Ira Sandi Tunny (Jurnal Ilmiah Kedokteran dan Kesehatan, 2022)
Hearing loss is a common problem experienced by everyone from time to time. Hearing loss is defined as a reduction in a person's ability to distinguish sounds. Hearing loss often occurs when fishermen dive. Hearing loss can be caused by impaired sound transmission in the outer ear or middle ear or what is known as conduction/conduction deafness and damage to the hair cells and nerve pathways or also called nerve deafness (Ganong, 2017), according to estimates from the World Health Organization (WHO) ,) 80% of people with hearing loss problems live in developing countries. In 2015 there were 120 million people with hearing loss worldwide. The purpose of this study was to determine the factors associated with hearing loss in traditional diving fishermen in Negeri Haya, Tehoru District, Central Maluku Regency in 2020. This study used a quantitative method, the research research design used in this study was quantitative research. Descriptive Analytic research design with a cross sectional design, the sample in the study was 92 people the research instrument used a questionnaire. SPSS Data Processing. Using the Chi-square test with a significant value of p=0.05. The results of this study obtained significant values ​​of working mass (p = 0.002), frequency (p = 0.014), depth (p = 0.047) from these results it was concluded that working mass, diving frequency,,